2008
DOI: 10.1667/rr0888.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Helzel and OxyLite Systems in the Measurements of Tumor Partial Oxygen Pressure (pO2)

Abstract: It has been demonstrated in both experimental and human malignancies that hypoxic tumor cells are linked with aggressive disease phenotype. One of the methods to identify these cells is by direct physical measurement of tumor pO 2 . This study compared pO 2 values measured with two systems, the Helzel Hypoximeter (successor of the polarographic Eppen-dorf electrode) and the OxfordOptronix OxyLite (fiber-optic probe), in R3327-AT and R3327-AT/tkeGFP tumors. Partial oxygen pressure was measured in individual tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…The manufacturer of the probe has stated that pO 2 measurements are insensitive to sample viscosity, and McNulty et al (2004) have also found this to be true for protein concentrations up to at least 30% (the highest value tested by the researchers, and the protein concentration that exists in the lens). Other investigators have used the fiber optic fluorescence probe to measure pO 2 levels in solid tissues such as kidney and tumors, and found the results to be comparable with those obtained with other O 2 -measuring instruments (Leong et al, 2008; Seddon et al, 2001; Wen et al, 2008). …”
Section: Discussionsupporting
confidence: 55%
“…The manufacturer of the probe has stated that pO 2 measurements are insensitive to sample viscosity, and McNulty et al (2004) have also found this to be true for protein concentrations up to at least 30% (the highest value tested by the researchers, and the protein concentration that exists in the lens). Other investigators have used the fiber optic fluorescence probe to measure pO 2 levels in solid tissues such as kidney and tumors, and found the results to be comparable with those obtained with other O 2 -measuring instruments (Leong et al, 2008; Seddon et al, 2001; Wen et al, 2008). …”
Section: Discussionsupporting
confidence: 55%
“…The probes are pre-calibrated by Oxford Optronics in solutions of multiple temperatures and PO 2 values. Although factors such as pH sensitivity have not been measured, the in vivo results compare favorably with electrode measurements of PO 2 , even in tumors where pH can vary considerably (Seddon et al, 2001; Wen et al, 2008). The chronically implantable fiber optic probe was constructed by Oxford Optronics based on a design supplied by Dr. Dunn.…”
Section: Methodsmentioning
confidence: 76%
“…Unlike the Eppendorf histogram electrode, these do not consume oxygen with each measurement; thus; continuous observations of oxygenation status in the same tumour region is possible (Griffiths and Robinson 1999). Preclinical studies comparing the commercially available Oxford-Optronix OxyLite sensor with the polarographic techniques (Collingridge et al 1997;Braun et al 2001;Seddon et al 2001;Wen et al 2008), or classical paired survival curve estimates of radiobiological hypoxia (Urano et al 2002), reported similarities and differences depending on the tissue type, tumour size or the changes observed using various modifiers of tumour hypoxia. Although fibre optic probes have the potential to not only measure the pretreatment level of tumour hypoxia, but also to monitor tumour oxygenation status continuously during and after treatment, there has as yet been no clinical application in cancer.…”
Section: Direct Measurements Of Tumour Oxygenationmentioning
confidence: 99%